De la Vieţile sfinţilor la Matematică: literatura princiară de limbă greacă în sec. al XVIII-lea - Lia Brad Chisacof (Revista de Istorie și Teorie Literară)
This article presents several works that belong to the panegyrical genre and parenetic literature, addressed to the young members of the ruling families.